Design parameters for a solar heating system with an underground cylindrical tank - Inalli, M (Pergamon-Elsevier Science Ltd, 1998)
We have performed a theoretical analysis of a solar heating system with an underground cylindrical tank. A two-dimensional ground-temperature distribution is used around the tank. Heat-transfer problems are solved by application of complex, finite-Fourier-transform technique and a finite difference method. A 25- and a 100-house community are considered for the performance calculation. The effects of collector area, tank volume, number of houses, and depth of the tank have been investigated far istanbul (40 degrees N). Isotherms of the ground around the tank are illustrated in graphical form. (C) 1998 Elsevier Science Ltd. All rights reserved.
Keywords: Storage; Model